Unilateral renal artery stenosis presenting as acute flaccid paralysis: a rare presentation. (31st August 2018) - Singh, Pradyumna Kumar; Rajput, Rajesh; Banerjee, Saurav; Garg, Keshav
Abstract : Renovascular hypertension is one of the common causes of secondary hypertension. Here we report a case of patient of renal artery stenosis presenting to the emergency department as a case of acute flaccid paralysis. Renal artery stenosis has been associated with hypokalaemia, but rarely reported to be symptomatic. Initial correction of hypokalaemia leads to improvement of weakness and aetiological work up for hypokalaemia with hypertension revealed hypokalaemia due to hyperaldosteronism secondary to unilateral renal artery stenosis. The patient was managed medically with aldosterone antagonist in the anti hypertensive therapy and weakness did not recur despite withdrawal of potassium supplements. On follow-up, the patient was ambulatory with no signs of weakness, controlled blood pressure and normal potassium level.